(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2024)
The higher education institutions are very vital to the development of the country. The Nigerian higher education is aimed at providing the manpower for the industrial sector in the country. It is unfortunate that this higher education is plagued with many challenges. This paper identified inadequate funding, inadequate lecturers, inadequate infrastructural facilities, unstable academic calendar, academic corruption, insecurity, brain-drain, weak leadership, COVID-19 challenge, poor research and poor staff development as the challenges facing the higher institutions in Nigeria. To address these challenges, the paper recommended that the government should provide: adequate funding for higher institutions, employment of more lecturers, provision of adequate infrastructural facilities, ensure stable academic calendar, fight academic corruption, provide adequate security, motivate lecturers, appoint competent leadership and provide adequate ICT facilities to schools to enable them switch to online education to reduce the impact of post COVID-19 on the higher institutions.